Seropositive juvenile rheumatoid arthritis: analysis of the spectrum of clinical manifestations and therapy according to a retrospective study - М. I. Kaleda; I. P. Nikishina; E. S. Fedorov; S. V. Arsenyeva; A. N. Shapovalenko (Современная ревматология)
Seropositive juvenile rheumatoid arthritis (JRA) is the rarest subtype of juvenile idiopathic arthritis (JIA) that is the equivalent of RA in adults and is manifested mainly by a symmetric polyarticular lesion, rapid structural disease progression with the formation of intraarticular erosions, the presence of positive rheumatoid factor (RF), and/or anti-cyclic citrullinated peptide (CCP) antibodies.Objective: to analyze demographic, clinical, and laboratory features of seropositive JRA and drug therapy according to a retrospective 10-year study.Patients and methods. The retrospective study enrolled patients diagnosed with seropositive JRA confirmed according to the ILAR classification, who were treated at the Childhood Rheumatology Department, V.A. Nasonova Research Institute of Rheumatology, from 2010 to 2020. Demographic indicators, data from clinical, laboratory, and instrumental examinations, and performed therapy were assessed.Results and discussion. The investigation enrolled 70 patients, amounting to 6.5% of the total number of patients with all clinical types of JIA. Among them, there was a great preponderance of girls (88.6%); the ratio of boys to girls was 1:7.8. The median age of onset of JRA was 12.2 [7.0; 14.0] years; the median duration of disease at diagnosis verification was 6 [4; 12] months; the median number of active joints at diagnosis of JRA was 16.5 [10.75; 23.25]; oligoarthritis was identified in 11.2% of patients at disease onset (within the first 6 months). During the first year of the disease, radiographic Stages II, III, and IV were defined in 42.9, 50, and 7.1%, respectively. Positive RF was found in 94.3% of patients; there was positivity for anti-CCP antibodies in 78.6%, a combination of positivity for RF and anti-CCP antibodies in 72.9%; only positive anti-CCR antibodies were seen in 5.7%. The median ESR at diagnosis verification was 29 [19.75; 44.5] mm/h; that of CRP was 15.0 [6.9; 34.4] mg/l. The extra-articular manifestations of the disease were found in 18 patients (25.7% of the total number of patients): fever in 5 (7.2%); lymphadenopathy in 17 (24.3%); lung damage in 3 (4.3%); rheumatoid nodules in 2 (2.9%); pericarditis in 1 (1.4%) patient, and uveitis in 1 (1.4%). Sjögren's syndrome was diagnosed in 25.7% of patients; autoimmune thyroiditis in 8.6%. A family history of autoimmune diseases was recorded in 22.8%. Nonsteroidal anti-inflammatory drugs and glucocorticoids were used in 97.1 and 48.6% of patients; respectively; the patients received synthetic disease-modifying antirheumatic drugs (sDMARDs): only methotrexate (MTX) [n=55 (78.6%)], sequentially 2 sDMARDs [n=10 (14.3%)], 3 sDMARDs [n=5 (7.1%)]; biological agents (BAs) [n=66 (94.2%)]. During the first year of the disease, Biological therapy was initiated because of the rapid progression of the erosive process in 78.6% of patients. 64.3% of children took one BA, 18.6 and 7.1% received two and three BAs, respectively. Abatacept (ABC) as the first BA was used most often (45.7%). The reasons for revision of therapy were its secondary inefficiency in most cases and serious adverse reactions in 4 patients (ABC- and infliximab-related infusion reactions in 2 cases and conversion of tubercular tests in 2). The differences in the anti-CCP antibody detection rate were statistically insignificant in the group that used only one BA effectively long and in the group that needed to switch to another BA. When choosing a BA, preference was given to tocilizumab or rituximab (RTM) in patients with seropositive JRA in the presence of systemic manifestations, and high clinical and laboratory activities and to RTM or ABC in those with detected Sjögren's syndrome.Conclusion. Seropositive JRA is a rare subtype of JIA that has an initially unfavorable course. Most patients require early aggressive therapy, including MTX and a BA due to the rapid progression of erosive arthritis. The presence of systemic manifestations and/or Sjögren's syndrome plays a defining role in choosing a specific BA. The presence of anti-CCP antibodies does not affect the selection or change of a BA.